A Dual‐Targeting Octaguanidine–Doxorubicin Conjugate Transporter for Inducing Caspase‐Mediated Apoptosis on Folate‐Expressing Cancer Cells. (15th March 2016) - Nair, Jyothi B.; Joseph, Manu M.; Mohapatra, Saswat; Safeera, M.; Ghosh, Surajit; Sreelekha, T. T.; Maiti, Kaustabh Kumar
Abstract: An efficient synthetic framework was assembled (G8‐FKE‐FA‐Dox), consisting of a lysosome‐targeting octaguanidine molecular transporter with a cathepsin B (cath B)‐specific peptide substrate, folic acid, and the potent chemotherapeutic drug doxorubicin (Dox). Because the folate receptor (FR) and cath B are overexpressed in malignant cells, this transporter conjugate successfully executed lysosome‐mediated transport of Dox to FR‐positive tumor cells, illustrating this framework as an excellent targeted drug delivery system (TDDS). G8‐FKE‐FA‐Dox was shown to exhibit selective toxicity toward FR‐overexpressing cancer cells, with an IC50 value superior to that of the USFDA‐approved Lipodox TM and proportional to that of free Dox via selective induction of apoptosis by the activation of caspases 8, 9, and 3. This TDDS was observed to be nontoxic to red blood cells and lymphocytes at neutral pH. Furthermore the tumor‐targeting dissemination pattern of this system was revealed by monitoring the in vivo biodistribution of the carrier (G8‐FKE‐FA‐FL) in normal and FR‐overexpressing tumor‐bearing mice. Abstract : A new G8 summit : An efficient dualtargeting octaguanidine transporter–doxorubicin (Dox) conjugate (G8‐FKE‐FA‐Dox) shows significantly higher cytotoxicity toward folate receptor (FR)‐ and cathepsin B‐overexpressing malignant cells than the USFDA‐approved Lipodox. Interestingly, G8‐FKE‐FA‐Dox exhibits negligible hemolysis effects toward red blood cells and induces extensive apoptosis. The selective biodistribution of the transporter (G8‐FKE‐FA‐FL) is reflected in FR‐positive tumor‐bearing mice.